Review of Evidence for Using Chest X-Rays for Active Tuberculosis Screening in Long-Term Care in Canada - Mariana Herrera Diaz; Mariana Herrera Diaz; Margaret Haworth-Brockman; Margaret Haworth-Brockman; Yoav Keynan; Yoav Keynan; Yoav Keynan (Frontiers Media S.A., 2020)
Background: People living in long-term care facilities (LTCF) are at high risk to develop active tuberculosis primarily as a result of reactivation of a latent TB infection, or endemic transmission between residents. Current national guidelines in Canada are to use a posterior-anterior and lateral chest X-ray to screen for TB for those over 65 years old, upon admission to a LTCF.Objective: To assess the available evidence for cost benefits of universal chest X-ray screening for new LTCF residents.Methodology: We conducted a search for all articles published until September 2018, in PubMed and WorlCat databases, in English, using a combination of key words: chest X-ray, chest radiography or CXR, long-term care, elderly, screening, and tuberculosis. We also reviewed publicly available guidelines for screening new residents to LTCF from across Canada. We report on a qualitative synthesis of the evidence in the documents retrieved.Results: The final review yielded four cost-effectiveness studies (2 of 4 conducted in countries with low incidence), one systematic review, one recommendation/editorial, and one cohort study. We found that in a tuberculosis low-incidence country the CXR cost per identified case was $672,298 CAD. Enacting a more targeted screening program, perhaps one that tests only those who previously had TB, or other high-risk medical conditions may enhance the cost-effectiveness.Recommendations: We suggest reviewing the screening policy for active TB in people entering LTCF, which is based on a CXR. The results indicate that a targeted search for active TB in people with symptoms or other high-risk medical conditions may be more cost-effective.